Nilai Perusahaan, Kinerja Lingkungan dan Konservatisme Akuntansi - Kodriyah Kodriyah; Denny Kurnia; Indah Nailatus Sa’adah; Yayah Kholiyah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This study aims to examine and prove the influence between environmental performance and accounting conservatism on company value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Methodology: Manufacturing Companies listed on the Indonesia Stock Exchange became the population in this study. Purposive sampling was used to determine samples and obtained as many as 50 companies that met the criteria. Multiple linear regression analysis tests the model and proves the proposed hypothesis. Data is processed with the help of Statistic tools. Results: The test result is that environmental performance can affect the value of the company and accounting conservatism cannot be proven to affect the value of the company Limitations: The limitations in this study prove that accounting conservatism variables measured by earnings / Accrual measure have no influence on company value, subsequent research can use other measurements for accounting conservatism so that it can prove its effect Contribution: The results of this study can contribute to investors' decision-making to consider aspects of the company's responsibility to the surrounding environment for its operating activities.